2011
DOI: 10.1111/j.1365-3083.2010.02481.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Cytotoxicity of NC‐2+ Cells Against the Growth and Metastasis of WEHI‐164 Fibrosarcoma

Abstract: We have previously reported a new receptor (NC‐2) for natural cytotoxicity (NC) on murine leucocytes, identified by monoclonal antibody D9 (mAb D9). Pretreatment of mouse spleen cells with different concentrations of mAb D9 in vitro blocked NC against WEHI‐164, whereas natural killing (NK) activity against YAC‐1 was unaffected. This paper reports the immune surveillance against the growth of WEHI‐164 tumour cells in mice by NC‐2+ Cells. The kinetics of in vivo reduction in NC activity were investigated by trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This suggestion is in line with earlier research that demonstrated how the poly(I:C) treatment initiated accumulation of active NK cells in the liver through the inducing of these cells to migrate from the spleen through to the liver [41]. These findings shed a light on the antitumour impact of poly(I:C) on metastatic tumours given that such tumours secrete interferon as we have previously shown [18,21,26,39] and that NK cells have a part in immune surveillance against cancerous cells [45] and that they are able to eradicate cancers from the liver [8,33]. These findings also contribute to future research in this area in further examining the impact of the poly(I:C) treatment against liver tumours when taken systemically or via hepatic portal injection.…”
Section: Discussionsupporting
confidence: 89%
“…This suggestion is in line with earlier research that demonstrated how the poly(I:C) treatment initiated accumulation of active NK cells in the liver through the inducing of these cells to migrate from the spleen through to the liver [41]. These findings shed a light on the antitumour impact of poly(I:C) on metastatic tumours given that such tumours secrete interferon as we have previously shown [18,21,26,39] and that NK cells have a part in immune surveillance against cancerous cells [45] and that they are able to eradicate cancers from the liver [8,33]. These findings also contribute to future research in this area in further examining the impact of the poly(I:C) treatment against liver tumours when taken systemically or via hepatic portal injection.…”
Section: Discussionsupporting
confidence: 89%
“…Globally, cancer is the leading cause of death, with almost 10 million deaths in 2020 [38]. Lycopene, a carotenoid, is an antioxidant and a singlet oxygen quencher that has been found to be protective against cancer in the prostate, testes, and skin, where it is concentrated; it also decreases oxidative stress and DNA damage [25,39,40]. Antioxidant nutraceuticals are primarily implicated in cancer, for example, β-carotene.…”
Section: Chronic Disease Preventionmentioning
confidence: 99%
“…In the past years, nutraceuticals received particular attention from consumers due to their potential to improve health, delay the aging process, increase life expectancy, prevent chronic diseases, and even support the structure or function of the body [3]. Different studies reported that nutraceuticals, such as ginseng, green tea, sumac, folic acid and cod liver oil, present promising results in different pathological complications, such as atherosclerosis [4,5], cardiovascular diseases [6,7], diabetes [8], cancer [9,10] and neurological disorders [11]. Furthermore, recently published reports demonstrated the positive effects of nutraceutical plants as Zizyphus jujube [12] or Lavandula officinalis [13] on the Alzheimer's disease, learning and memory.…”
Section: Introductionmentioning
confidence: 99%